2020
DOI: 10.1021/acsomega.0c02518
|View full text |Cite|
|
Sign up to set email alerts
|

Biological Effects of Titanium Surface Charge with a Focus on Protein Adsorption

Abstract: The effect of changes in surface charge on the biological properties of implants is not clear. The objective of this study was to evaluate the biological properties of the surface of titanium sheets with different charges due to different treatment methods. Titanium sheets were sandblasted with large grit and underwent acid etching before being subsequently divided into the following groups: SLA, no further treatment; SLA-Ca 2+ , immersed in 1% CaCl 2 solution; SLA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…As we observed in this study, a negatively charged surface could inhibit bacterial adhesion to the surface. In contrast, a positively charged surface could facilitate the integration of biomaterial into soft tissues as reported elsewhere. Our intended application in the oral cavity involves the negatively charged surface facing outwards (exposed to saliva and bacterial insults) and the positively charged surface facing inwards (toward tissue). This may allow us to synergistically integrate the two functions of our BTO-nanocomposites by placing them accordingly, thereby tackling two major issues in prostheticsbacterial contamination and tissue integration.…”
Section: Discussionmentioning
confidence: 98%
“…As we observed in this study, a negatively charged surface could inhibit bacterial adhesion to the surface. In contrast, a positively charged surface could facilitate the integration of biomaterial into soft tissues as reported elsewhere. Our intended application in the oral cavity involves the negatively charged surface facing outwards (exposed to saliva and bacterial insults) and the positively charged surface facing inwards (toward tissue). This may allow us to synergistically integrate the two functions of our BTO-nanocomposites by placing them accordingly, thereby tackling two major issues in prostheticsbacterial contamination and tissue integration.…”
Section: Discussionmentioning
confidence: 98%
“…In recent years, several researchers found that changing the charge state on the surface of implants affects their interactions with proteins as well as cells. 37 The role of polyanions in osteogenesis and mineralization has been studied by many researchers. Chondroitin sulfate A is a natural polyanionic substance, and research indicates that it can promote the maturation of osteoblasts in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Many extracellular proteins in the body, such as albumin, albumin, fibronectin and laminin, have isoelectric points less than 7 and are negatively charged under physiological conditions. Therefore, positively charged surfaces can affect cell adhesion, proliferation and differentiation by increasing protein adsorption, thereby promoting bone formation [53][54][55]. Secondly, the electric field formed by the surface charge of the material can also affect the concentration of intracellular Ca 2þ by affecting the voltage-gated calcium channel, thus affecting the osteogenic differentiation of MSC [56,57].…”
Section: Surface Charge Affects Osteogenesis Through Protein Adsorpti...mentioning
confidence: 99%